Pengaruh Pola Asuh Islami Terhadap Kenakalan Remja - Muhammad Rifald; Zahro Varisna Rohmadani (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Islamic parenting is the attitude and behavior of parents towards children from an early age, from the stage of teaching, developing, adapting and educating children referring to the Qur'an and al-Hadith (Asuh et al., 2017). The Islamic parenting style provided by parents also has an impact on children's behavior so that it can trigger good or bad behavior in a child, this can influence the occurrence of juvenile delinquency. This research aims to identify the influence of Islamic parenting on juvenile delinquency. The method used was quantitative correlational analysis by collecting data through questionnaires using a Google from link which was distributed to 123 respondents with ages according to the National Population and Family Planning Agency (BKKBN), namely 10-24 years. The sampling technique applied is quota Sampling. Data analysis was carried out using Product Moment correlation with SPSS version 23. The results showed that the correlation coefficient was negative, namely -0.514, so the correlation between the two variables was inverse so that the higher the Islamic parenting style, the lower the juvenile delinquency. the higher the rate of juvenile delinquency.